2-[2-(Aziridin-1-yl)ethyl]-5,5-dimethyl-2,5-dihydro-4H-benzo [e]isoindol-4-one (Cytotoxic Oxonaphthalene-Pyrroles, Part IV) - Helmut Spreitzer; Christiane Puschmann (Molbank, 2012)
An aziridine-containing side chain is attached to an oxonaphthalene-annelated pyrrole in expectation of DNA alkylating properties. The cytotoxicity is evaluated against two cell lines, KB-31 and KB-8511, respectively.